Comparison of three different insertion techniques with LMA-UniqueTM in adults: results of a randomized trial - Eglen,Merih (2017)
Abstract Background The triple airway maneuver insertion technique allowed faster insertion of the LMA. This study compared three different insertion techniques of the laryngeal mask airway-UniqueTM. Methods One hundred and eighty ASA I-II patients aged 18-65 years were included into the study. Patients were randomly allocated to the standard, rotational and triple airway maneuver (triple) group. In the standard group (n = 60), the LMA (Laryngeal Mask Airway) was inserted with digital intraoral manipulation. In the triple group (n = 60), the LMA was inserted with triple airway maneuver (mouth opening, head extension and jaw thrust). In the rotational group (n = 60), LMA was inserted back-to-front, like a Guedel airway. Successful insertion at first attempt, time for successful insertion, fiber optic assessment, airway morbidity and hemodynamic responses were assessed. Results Successful insertion at the first attempt was 88.3% for the standard, 78.3% for the rotational and 88.3% for the triple group. Overall success rate (defined as successful insertion at first and second attempt) was 93% for the standard, 90% for the rotational and 95% for the triple group. Time for successful insertion was significantly shorter in the triple group (mean [range] 8.63 [5-19]s) compared with the standard (11.78 [6-24]s) and rotational group (11.57 [5-31]s). Fiber optic assessment, airway morbidity and hemodynamic responses were similar in all groups. Conclusions Rotational and triple airway maneuver insertion techniques are acceptable alternatives. Triple airway maneuver technique shows higher overall success rates and allows shorter insertion time for LMA insertion and should therefore be kept in mind for emergent situations.